Proceedings of the 15th ACM International Conference on Modeling, Analysis and Simulation of Wireless and Mobile Systems 2012
DOI: 10.1145/2387238.2387265
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating resistance to jamming and casual interception in mobile wireless networks

Abstract: Mobile ad-hoc and sensor networks play an important role in several application fields. The usage of wireless links and the node mobility make the networks prone to security attacks; among these, jamming attacks are insidious and they consist of one or more nodes continuously transmitting dummy packets to keep some wireless links busy. The goal is to destroy the network connectivity or highly reduce its throughput. In this paper we propose a probabilistic formal method, based on a process algebraic approach, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Gallina et al [19] have concentrated on the analysis of connectivity and the evaluation of interference in mobile networks and have proposed a probabilistic formal method, based on a process algebraic approach. They have considered the jamming attacks and have applied their framework for the analysis of an indoor wireless communication scenario.…”
Section: Related Workmentioning
confidence: 99%
“…Gallina et al [19] have concentrated on the analysis of connectivity and the evaluation of interference in mobile networks and have proposed a probabilistic formal method, based on a process algebraic approach. They have considered the jamming attacks and have applied their framework for the analysis of an indoor wireless communication scenario.…”
Section: Related Workmentioning
confidence: 99%
“…Very recent research, in [28], suggested a frame-work to identify jammers in MANET environment. Research was conducted also in [29,30] to find ways to overcome this physical attack.…”
Section: Counter Measuresmentioning
confidence: 99%